Bright young women [compact disc, unabridged] - Knoll, Jessica (Simon & Schuster Audio, 2023)
January 1978. A serial killer has terrorized women across the Pacific Northwest, but his existence couldn't be further from the minds of the vibrant young women at the top sorority on Florida State University's campus in Tallahassee. Tonight is a night of promise, excitement, and desire, but Pamela Schumacher, president of the sorority, makes the unpopular decision to stay home, a decision that unwittingly saves her life. Startled awake at 3 a.m. by a strange sound, she makes the fateful decision to investigate. What she finds behind the door is a scene of implausible violence, two of her sisters dead; two others, maimed. Over the next few days, Pamela is thrust into a terrifying mystery inspired by the crime that's captivated public interest for more than four decades. On the other side of the country, Tina Cannon has found peace in Seattle after years of hardship. A chance encounter brings twenty-five-year-old Ruth Wachowsky into her life, a young woman with painful secrets of her own, and the two form an instant connection. When Ruth goes missing from Lake Sammamish State Park in broad daylight, surrounded by thousands of beachgoers on a beautiful summer day, Tina devotes herself to finding out what happened to her. When she hears about the tragedy in Tallahassee, she knows it's the man the papers refer to as the All-American Sex Killer. Determined to make him answer for what he did to Ruth, she travels to Florida on a collision course with Pamela, and one last impending tragedy.